2014
DOI: 10.1080/00140139.2014.968634
|View full text |Cite
|
Sign up to set email alerts
|

Muscular activity of lower limb muscles associated with working on inclined surfaces

Abstract: This study investigated effects of visual cues, muscular fatigue, task performance and experience of working on inclined surfaces on activity of postural muscles in the lower limbs associated with maintaining balance on three inclined surfaces—0°, 14° and 26°. Normalized electromyographic (NEMG) data were collected on 44 professional roofers bilaterally from the rectus femoris, biceps femoris, tibialii anterior, and gastrocnemii medial muscle groups. The 50th and 95th percentile normalized EMG amplitudes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Consistent with this finding, the results of the current study further pointed out that standing on a sloped surface could result in increased randomness but decreased complexity in the directional coupling of COP compared with the horizontal surface. The changes in bidirectional coupling of COP could be associated with increased postural instability 37,38 and direction-specific sway 38 , and would be resultant from the alteration of reference frame regarding gravity, support surface and posture orientation 16,17 , or the different muscle activations and synergies contributing to ankle stiffness 18,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, the results of the current study further pointed out that standing on a sloped surface could result in increased randomness but decreased complexity in the directional coupling of COP compared with the horizontal surface. The changes in bidirectional coupling of COP could be associated with increased postural instability 37,38 and direction-specific sway 38 , and would be resultant from the alteration of reference frame regarding gravity, support surface and posture orientation 16,17 , or the different muscle activations and synergies contributing to ankle stiffness 18,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Reference [44] also studied visual effect, muscular fatigue, task performance and working experience on inclined surfaces on activity of lower limb postural muscles rectus femoris, biceps femoris, tibialii anterior and gastrocnemii medial muscle groups associated with maintaining balance by normalised electro myo graphic (NEMG) data.…”
Section: Muscle Activity During Gaitmentioning
confidence: 99%
“…Some studies using surface electromyogram (EMG) examination have shown an increased activity of the soleus and the gastrocnemius while the feet are in plantar flexion [ 8 , 13 , 15 ]. A higher activity of the tibialis anterior associated with a dorsiflexion of the feet has also been described [ 8 , 16 ], but not systematically [ 13 , 15 ]. It should also be noted that most of these studies used high-sloping angles greater than or equal to 14°, which are often encountered in roofing [ 9 , 11 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher activity of the tibialis anterior associated with a dorsiflexion of the feet has also been described [ 8 , 16 ], but not systematically [ 13 , 15 ]. It should also be noted that most of these studies used high-sloping angles greater than or equal to 14°, which are often encountered in roofing [ 9 , 11 14 , 16 ]. A few studies use 10° as the minimum value [ 8 , 15 ], yet this angle is greater than the usual walkway slope, whose standard is at 4.76° [ 17 ].…”
Section: Introductionmentioning
confidence: 99%